2015
DOI: 10.1016/j.cej.2015.01.136
|View full text |Cite
|
Sign up to set email alerts
|

Full scale evaluation of combined sewer overflows disinfection using performic acid in a sea-outfall pipe

Abstract: (2015). Full scale evaluation of combined sewer overflows disinfection using performic acid in a sea-outfall pipe. Chemical Engineering Journal, 270, 133-139. https://doi.org/10.1016Journal, 270, 133-139. https://doi.org/10. /j.cej.2015 AbstractPollution of surface waters with pathogens from combined sewer overflows limits recreational use of surface waters. Large retention basins are a satisfactory solution but they are rarely sufficient for economic or space reasons. Fast disinfection during the overflow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…However, in a recent comparison study, PFA required a significantly shorter contact time than PAA: 20 and 360 mins, respectively, when a similar dose (2-5 mg/L) was used [136]. PFA was also studied in a fullscale experiment (1-8 mg/L and a contact time of 24 mins), which confirmed that the EU bathing water microbial quality was possible to be reached with the method after taking into account dilution to the receiving water body [137]. Tondera et al [35] used PFA (at 12-24 mg/L, and with a 10-minute contact time) for CSO and obtained a 1.8-3.1 log 10 reduction of E. coli, total coliform bacteria, intestinal enterococci, Aeromonas s, P. aeruginosa, and somatic coliphages, whereas G. lamblia and human viruses (human adenovirus, polyomavirus, norovirus, rotavirus, and enterovirus) were not inactivated.…”
Section: Combined Sewer Overflowmentioning
confidence: 67%
“…However, in a recent comparison study, PFA required a significantly shorter contact time than PAA: 20 and 360 mins, respectively, when a similar dose (2-5 mg/L) was used [136]. PFA was also studied in a fullscale experiment (1-8 mg/L and a contact time of 24 mins), which confirmed that the EU bathing water microbial quality was possible to be reached with the method after taking into account dilution to the receiving water body [137]. Tondera et al [35] used PFA (at 12-24 mg/L, and with a 10-minute contact time) for CSO and obtained a 1.8-3.1 log 10 reduction of E. coli, total coliform bacteria, intestinal enterococci, Aeromonas s, P. aeruginosa, and somatic coliphages, whereas G. lamblia and human viruses (human adenovirus, polyomavirus, norovirus, rotavirus, and enterovirus) were not inactivated.…”
Section: Combined Sewer Overflowmentioning
confidence: 67%
“…In parallel after 60 min of contact time residual PAA from sample was quenched by adding 100 mg·L -1 sodium thiosulphate followed by 50 mg·L -1 catalase as described by Chhetri et al, (2014) from sample to enumerate Enterococcus. Our previous study on disinfection of E. coli and Enterococcus from CSO water showed that Enterococcus was more difficult to disinfect from CSO sample with respect to E. coli (Chhetri et al, 2015(Chhetri et al, , 2014. Therefore, disinfection of Enterococcus was only considered in this study.…”
Section: Experiments Performedmentioning
confidence: 99%
“…Recently we investigated in laboratory scale the possibility to use peracetic acid and performic acids for disinfection of CSO in terms of doses required for disinfection, kinetic of reaction in water and residual disinfectants (Chhetri et al, 2014). The first full scale demonstration of performic acid disinfection of CSO was just described using a sea outfall pipe north of Copenhagen, Denmark as reaction tank (Chhetri et al, 2015). The disinfection efficiency can be influenced by inlet water quality since disinfectant will react with other contaminant in untreated water.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, higher concentration of PAA (~30 mg/L and ~10 mg/L) was not completely degraded after 72 h. PFA and chlorine dioxide are unstable disinfectants. Faster degradation of PFA was observed than PAA when it was used to disinfect combined sewer overflows (Chhetri et al, 2015(Chhetri et al, , 2014 and similarly, faster degradation chlorine dioxide was observed when it was used to remove pharmaceuticals in biologically treated wastewater (Hey et al, 2012). Even though all three alternative disinfectants were almost completely degraded during the first 24 hours of the algal test, clear concentration-response patterns were obtained during the 72 hours incubation (Fig 1).…”
Section: Resultsmentioning
confidence: 89%
“…In recent years, PFA has been used to disinfect primary and secondary WWTP effluents (Gehr et al, 2009;Ragazzo et al, 2013) and to disinfect combined sewer overflows (Chhetri et al, 2015). PFA is unstable and needs to be generated on-site, when needed, as a quaternary equilibrium mixture of performic acid (PFA), formic acid, hydrogen peroxide and water:…”
Section: Introductionmentioning
confidence: 99%